Aspek Hukum Terhadap Pengawasan Pemerintah atas Penyertaan Modal Negara Dalam Rights Issue di BUMN - Naufan Mufti Sudarmono (Indonesian Journal Publisher, 2023)
State Owned Enterprises (BUMN) are state companies whose capital comes from separated state assets. The state as an investor in the formation of BUMN still has a role in supervising through institutions that have been given authority which are carried out by the government in a broad sense which includes not only executive institutions but also legislative institutions. In its development, every company including BUMN requires capital. The type of research used is normative juridical research which examines statutory products and other literature relating to government supervision and control of state capital participation in rights issues conducted by BUMN. There are at least provisions governing Government Supervision and control over state equity participation in rights issues in BUMN, including Law Number 19 of 2003 concerning State-Owned Enterprises by the Ministry of BUMN, State Treasury Law No. 1 of 2004 by BPK, and Law -Law 1945 Article 20A paragraph 1 whereby the DPR carries out the oversight function and the budget function which is carried out when the government wants to invest state capital into BUMN through the APBN mechanism.